2020
DOI: 10.1093/nutrit/nuaa123
|View full text |Cite
|
Sign up to set email alerts
|

Low-calorie sweeteners and human health: a rapid review of systematic reviews

Abstract: Introduction Low-calorie sweeteners are increasingly prevalent in the food supply and their consumption has increased in recent decades. Although low-calorie sweeteners approved for use are considered safe from a toxicological perspective, their short- and long-term impacts on chronic disease risk remain uncertain. The aim of this review was to summarize the evidence from systematic reviews on low-calorie sweetener use and chronic conditions and risk factors in children and adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…In past studies, we used retroactive 10-y weight history—another component of NHANES—to show that previously expressed desire to lose/control body weight was linked to higher LCS use [ 16 ]. That study counters the still-repeated arguments that LCS leads to weight gain and is a causal factor in the development of obesity [ 8 , 11 , 12 ]; assertions that were not confirmed in recent systematic reviews [ 34 , 35 ] It is important to note here that obesity is a recognized risk factor for many cancers that may be unrelated to LCS use.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In past studies, we used retroactive 10-y weight history—another component of NHANES—to show that previously expressed desire to lose/control body weight was linked to higher LCS use [ 16 ]. That study counters the still-repeated arguments that LCS leads to weight gain and is a causal factor in the development of obesity [ 8 , 11 , 12 ]; assertions that were not confirmed in recent systematic reviews [ 34 , 35 ] It is important to note here that obesity is a recognized risk factor for many cancers that may be unrelated to LCS use.…”
Section: Discussionmentioning
confidence: 51%
“…Assigning participants to LCS consumers and nonconsumer groups can be problematic—even two-day intakes are not representative of habitual consumption. In general, randomized controlled trials make for a higher standard of evidence [ 35 , 37 ]. Secondly, LCS beverages and foods are not flagged and need to be searched for in FNDDS, the USDA nutrient composition data file, using custom designed coding.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies (and the reviews citing them) lean toward finding adverse associations of LES with metabolic health outcomes, whereas RCTs lean toward neutral or beneficial effects, often for the same outcomes, such as body weight [ 40 , 41 ]. Large, well-designed observational studies with appropriate analyses can highlight legitimate areas of concern, although there is considerable debate around the use and limitations of observational data in nutrition [ 30 ].…”
Section: Perspectivementioning
confidence: 99%
“…11 In high-income countries, limited observational studies suggested a positive association between SFB intake and childhood obesity, while conflicting findings were reported from randomized controlled trials (RCTs). [12][13][14] The research beyond high-income countries is relatively less. 15 Additionally, these studies mainly addressed general obesity based on anthropometric measurements but failed to consider body fat distributions, which require the data on body composition, such as body fat percentage (BF%) and visceral fat area (VFA).…”
Section: Introductionmentioning
confidence: 99%